Kinematics and Dynamics Analysis of a 3-DOF Upper-Limb Exoskeleton with an Internally Rotated Elbow Joint - Xin Wang; Qiuzhi Song; Xiaoguang Wang; Pengzhan Liu (Applied Sciences, 2018)
The contradiction between self-weight and load capacity of a power-assisted upper-limb exoskeleton for material hanging is unresolved. In this paper, a non-anthropomorphic 3-degree of freedom (DOF) upper-limb exoskeleton with an internally rotated elbow joint is proposed based on an anthropomorphic 5-DOF upper-limb exoskeleton for power-assisted activity. The proposed 3-DOF upper-limb exoskeleton contains a 2-DOF shoulder joint and a 1-DOF internally rotated elbow joint. The structural parameters of the 3-DOF upper-limb exoskeleton were determined, and the differences and singularities of the two exoskeletons were analyzed. The workspace, the joint torques and the power consumption of two exoskeletons were analyzed by kinematics and dynamics, and an exoskeleton prototype experiment was performed. The results showed that, compared with a typical anthropomorphic upper-limb exoskeleton, the non-anthropomorphic 3-DOF upper-limb exoskeleton had the same actual workspace; eliminated singularities within the workspace; improved the elbow joint force situation; and the maximum elbow joint torque, elbow external-flexion/internal-extension and shoulder flexion/extension power consumption were significantly reduced. The proposed non-anthropomorphic 3-DOF upper-limb exoskeleton can be applied to a power-assisted upper-limb exoskeleton in industrial settings.